The Burden of Cardiomyopathy on Character Building in A Man Called Otto (2022) : Directed By Marc Foster - Muhamad Ridwan Tias; Ivanza Kenji Sakkay; Yanti Rosainah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores the influence of cardiomyopathy on character development as depicted through Otto Anderson in A Man Called Otto (2022). Employing thematic and qualitative analysis, the research examines the interplay between chronic illness, personal adversity, and moral transformation. Otto's journey, shaped by hypertrophic cardiomyopathy, highlights the dual burden of physical limitations and emotional distress. Through interactions with his community and his struggle with grief, Otto evolves from isolation to empathy, underscoring how adversity and social support can foster resilience. The findings illuminate the complex pathways through which chronic health conditions impact character and moral values, contributing to a deeper understanding of illness-driven growth and transformation.